2022
DOI: 10.1021/acsaem.2c02793
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin NiPt Single-Atom Alloy for Synergistically Accelerating Alkaline Hydrogen Evolution

Abstract: Single-atom Pt-based catalysts display a promising strategy to enhance the atomic utilization of noble metals while attaining desirable electrocatalytic properties. Moreover, rationally selecting the substrate helps optimize the water dissociation energy as well as promote H* conversion. Herein, we dispersed monoatomic Pt with ultralow content onto porous nickel nanosheets to accelerate the reaction kinetics of the hydrogen evolution reaction in an alkaline medium. Density functional theory calculations reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Hu and coauthors reported an HER catalyst using porous Ni(OH) 2 nanosheets with Pt loading and then annealing the previous catalyst to get a NiPt alloy catalyst. 84 The X-ray powder diffraction (XRD) spectra show the difference of Ni 2p and Pt 4s between Pt–Ni(OH) 2 and the NiPt alloy, which reveals a lower oxidation state of Pt single atom in NiPt. The new Ni–Pt bridge sites provide a low H binding energy, and Ni–Ni bright sites can adsorb H 2 O in the alkaline condition.…”
Section: Intrinsic Activity Of Single Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Hu and coauthors reported an HER catalyst using porous Ni(OH) 2 nanosheets with Pt loading and then annealing the previous catalyst to get a NiPt alloy catalyst. 84 The X-ray powder diffraction (XRD) spectra show the difference of Ni 2p and Pt 4s between Pt–Ni(OH) 2 and the NiPt alloy, which reveals a lower oxidation state of Pt single atom in NiPt. The new Ni–Pt bridge sites provide a low H binding energy, and Ni–Ni bright sites can adsorb H 2 O in the alkaline condition.…”
Section: Intrinsic Activity Of Single Sitementioning
confidence: 99%
“…The single-atom alloy catalyst can greatly increase the density of the metal active sites while considering their synergistic effects. Hu and coauthors reported an HER catalyst using porous Ni­(OH) 2 nanosheets with Pt loading and then annealing the previous catalyst to get a NiPt alloy catalyst . The X-ray powder diffraction (XRD) spectra show the difference of Ni 2p and Pt 4s between Pt–Ni­(OH) 2 and the NiPt alloy, which reveals a lower oxidation state of Pt single atom in NiPt.…”
Section: Intrinsic Activity Of Single Sitementioning
confidence: 99%
“…As shown in Figure 12, Hu's group fabricated Ni(OH) 2 nanoarrays following a hydrothermal method. 151 The obtained samples were then subjected to a second hydrothermal reaction using a Pt precursor to yield Pt−Ni(OH) 2 . The samples were then annealed and reduced in an atmosphere of Ar/H 2 to yield porous NiPt alloy nanosheets with ultralow Pt loading (Figure 12b).…”
Section: Phase Engineeringmentioning
confidence: 99%
“…As shown in Figure , Hu’s group fabricated Ni­(OH) 2 nanoarrays following a hydrothermal method . The obtained samples were then subjected to a second hydrothermal reaction using a Pt precursor to yield Pt–Ni­(OH) 2 .…”
Section: Design Strategies For Pt-based Alloysmentioning
confidence: 99%
See 1 more Smart Citation